(untitled) (RIVISTA ITALIANA DI PALEONTOLOGIA E STRATIGRAFIA, 1998)
An isolated phytosaur skull found in the Calcare di Zorzino (Norian, Late Triassic), near the locality of Endenna (Bergamo Prealps, Lombardy, Northern Italy), is described. The skull lacks the mandible and is severely compressed and distorted in its posterior portion. Nevertheless it is possible to ascribe it to the genus Mystriosuchus, likely to Mystriosuchus planirostris, already known on the basis of excellent specimens from the Stubensandstein Formation in Germany. This finding represents one of the rare large reptile specimens found in the Norian fossil-bearing localities of Lombardy, along with a new phytosaur yet to be prepared and a nearly two meters long specimen of the placodont Psephoderma alpinum.